National Education Policy and Indian Languages (ShodhVarta, 2022)
In July 2020, the "National Education Policy 2020" was approved by the Central Government to bring about the expected changes in the Indian education system according to the needs of modern times. Former ISRO chief Dr. K. It has been prepared on the basis of the recommendations of the committee headed by Kasturirangan. In the National Education Policy, emphasis has been laid on awakening the creative potential of the students through art, culture and language. Keeping Indian languages in mind, important provisions and suggestions have been given in the National Education Policy 2020 in Chapter-4 titled “Multilingualism and the power of language” and Chapter 22 titled “Promotion of Indian Languages, Art and Culture”. Language is not only the medium of expression, but it is also the vehicle of self-respect of any nation and its ancient civilization and culture. There are many languages and dialects in the country of India. 22 Indian languages have been given a place in the 8th Schedule of the Indian Constitution. Apart from this, according to the census of 2011, there are 1369 languages including dialects, in which 121 languages are spoken by more than 10 thousand people.